The Effect of Concentration and Organic Fertilizer on Pakcoy Plant Growth and Yield with Wick Hydroponic System - Januar Ramadhan; M Abror (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the growth and yield of Pakcoy plants with nutrient concentasry and liquid organic fertilizer in the Wicksist hydroponics system. The study was carried out on February 14, 2022 – April 14, 2022 at Green House Umsida using a randomized design method of groups with a single factor, namely a combination of ab mix nutrient concentration and liquid organic fertilizer consisting of 4 levels: AB Mix Nutrient Concentration 2000 ppm + Without POC, AB Nutrition Mix Concentration 1500 ppm + POC 500 ppm, Ab Mix Nutrient Concentration 1000 ppm + POC 1000 ppm, Ab Mix Nutrient Concentration 500 ppm + POC 1500 ppm. Observation of plant height, weevil diameter, leaf julah, wet weight and dry weight. The results of this study showed that the combination of AB MIX nutrients with liquid organic fertilizer from leri water fermented by lactobacilus bacteria affected the growth and production of mustard crops. On the K3 treatment (Ab Mix Nutrient Concentration 1000 ppm + POC 1000 ppm) had a significant influence on all observations. Providing a balanced concentration of nutrients with liquid organic fertilizers reduces the use of chemical fertilizers